Assessment of the magnitude, economic impact, and factors associated with expired veterinary pharmaceuticals in animal health facilities in South Wollo, Ethiopia - Yesuneh Tefera Mekasha; Ermias Belay Mekonnen; Abebe Tesfaye Gessese; Kassahun Berrie; Achenef Melaku Beyene; Bereket Dessalegn (Frontiers in Veterinary Science)
BackgroundThe issue of veterinary pharmaceutical expiration is a significant concern in animal health facilities globally. The existence of veterinary pharmaceutical expiration can be mainly associated with inadequate inventory control, store management, and a lack of effective pharmaceutical regulatory policies and guidelines. Hence, the study aimed to evaluate expired veterinary pharmaceuticals’ scope, economic impact, and contributing factors.MethodsA cross-sectional, explanatory sequential study design involving a mixed quantitative and qualitative approach was employed among 13 animal health facilities from March 2022 to December 2023 in and around Dessie town, South Wollo, Ethiopia. A key informant interview guide was used to retrieve the qualitative data that were analyzed through thematic content analysis. Then, the collected data were coded and analyzed using SPSS version 25. A mean score was used to determine the critical factors associated with veterinary pharmaceutical expiration.ResultsThe study found that the magnitude of expired veterinary pharmaceuticals in the fourth fiscal year was 7%. This wastage rate of veterinary pharmaceuticals led to a loss of approximately 69,564.54 USD. From expired veterinary pharmaceutical unit pack perspectives, approximately 403-unit packs (66%) expired in veterinary clinics, resulting in a loss of approximately 38,229.33 USD, and 209-unit packs (34%) expired in private veterinary pharmacies, incurring a loss of approximately 31,335.22 USD. From Anatomical Therapeutic Classification (ATC), antibiotics accounted for 14.8% of the total financial loss. Additionally, approximately 53% of liquid dosage forms were expired. The quantitative study identifies the lack of an information system and necessary software, poor store management, and lack of strict accountability as critical contributors to veterinary pharmaceutical expiration. Additionally, inadequate inventory management systems and a lack of adherence to established policies and guidelines for managing veterinary pharmaceutical expiration were the most vital contributors as key informants cited.ConclusionThe financial burden associated with expired veterinary pharmaceuticals exceeded the permissible threshold of 2%, indicating a significant concern for animal health budgets and the aquatic environment. This study underlines that the issue of veterinary pharmaceutical expiration is a critical problem that necessitates policy implications. To mitigate the expiration rate of veterinary pharmaceuticals, collaboration among multidisciplinary veterinary professionals, the Ethiopian Agricultural Authority, pharmaceutical supply chain agency, and researchers is essential.